2015
DOI: 10.1016/j.apcatb.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Cu and Fe modified derivatives of 2D MWW-type zeolites (MCM-22, ITQ-2 and MCM-36) as new catalysts for DeNO x process

Abstract: Zeolites with MWW topology (MCM-22, ITQ-2 and MCM-36) exchanged with copper and iron were studied as catalysts for selective catalytic reduction of NO with ammonia. It was shown that delamination and pillaring of layered MCM-22 zeolite resulted in the formation of ITQ-2 and MCM-36, respectively. Both these materials were characterized by MWW topology and significant contribution of mesopores.In a series of the zeolite based catalyst the most promising results in a process of selective catalytic reduction of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…Introduced copper occupied not only the ion-exchange positions but also formed small oligomeric or bulky CuO species on the samples surface. Similar observations were done in the previous studies concerning Cu-modified MCM-22 zeolite [18]. The highest values (also the highest increase in acidity) of CA were obtained for the samples desilicated for 2 h, which, as it was shown by AAS measurements, were loaded with the highest Cu content (the highest Cu/Al ratio).…”
Section: Characteristics Of the Cu-modified Samplessupporting
confidence: 89%
See 1 more Smart Citation
“…Introduced copper occupied not only the ion-exchange positions but also formed small oligomeric or bulky CuO species on the samples surface. Similar observations were done in the previous studies concerning Cu-modified MCM-22 zeolite [18]. The highest values (also the highest increase in acidity) of CA were obtained for the samples desilicated for 2 h, which, as it was shown by AAS measurements, were loaded with the highest Cu content (the highest Cu/Al ratio).…”
Section: Characteristics Of the Cu-modified Samplessupporting
confidence: 89%
“…The investigations on the catalytic efficiency of mesoporous zeolites in the DeNOx process showed their higher activity and stability in comparison to conventional microporous zeolites. Zeolites with the hierarchical porous structure were found to be more active at high temperatures (at which conventional zeolites promote ammonia oxidation) and in long term stability tests [13][14][15][16][17][18]. Various mesoporous zeolites with different pore structure, such as ZSM-5 [13][14][15][16][17], ZSM-12 [17], ITQ-2 or MCM-36 [18] were examined in the NH3-SCR process.…”
Section: )4 No + 4 Nh3 + O2 → 4 N2 + 6 H2omentioning
confidence: 99%
“…The system is highly active in the SCR process, but the use of noble metals in nitric acid plants is operationally unfavorable due to the high cost of the catalysts and their low selectivity to N 2 [19][20][21]. Many innovative supports have been proposed in the scientific literature so far, such as acti-vated carbon [22,23], carbon nanotubes [24,25], layered double hydroxides [26,27], layered clays [28][29][30][31], and zeolites [32][33][34][35][36]. Among them, significant attention was paid to zeolites that are microporous aluminosilicate minerals, either naturally occurring or industrially produced on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Corma and co-workers [28] found that Cu/MCM-22 zeolites were active catalysts with relatively high hydrothermal stability in selective catalytic reduction of NO with propane. Rutkowska and co-workers [29] found that Cu/MCM-22 zeolites could reach about 75% NO conversion with >90% N 2 selectivity at only 180 • C in NH 3 -SCR. In addition, Cu/MCM-22 zeolites could still maintain 100% NO conversion and >90% N 2 selectivity at 250-450 • C after hydrothermal aging in air with H 2 O at 550 • C for 3 h, which indicated that they were potential catalysts in NH 3 -SCR with good hydrothermal stability.…”
Section: Introductionmentioning
confidence: 99%